Pengaruh Komunikasi Organisasi Terhadap Kinerja Karyawan Di PT Das Map Indonesia - Wina Ayu Pratiwi; Flora Meliana Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Organizational communication plays an important role in supporting the flow of information, coordination, and teamwork, which can influence employee performance in achieving organizational goals. Therefore, this study aims to examine the influence of organizational communication on employee performance at PT Das Map Indonesia. The research employed a mixed methods approach by combining quantitative and qualitative methods. Quantitative data were collected through questionnaires distributed to 37 employees using the census sampling technique, while qualitative data were obtained through interviews with the Director of PT Das Map Indonesia and one employee, supported by observation and documentation. Quantitative data were analyzed using SPSS version 29 through validity, reliability, normality, simple linear regression, coefficient of determination, and hypothesis testing. The results show that organizational communication has a positive and significant effect on employee performance, with a t-value of 4.767, which is higher than the t-table value of 2.030, and a significance value below 0.05. The R Square value of 0.394 indicates that organizational communication contributes 39.4% to employee performance, while the remaining 60.6% is influenced by other factors outside this study. Keywords: Organizational Communication, Employee Performance.